(untitled) (Світ фінансів, 2017)
Горин В. П. Теоретичні засади неподаткових надходжень бюджету. Узагальнено наукові підходи до трактування сутності неподаткових надходжень бюджету та вказано на дискусійні моменти. Проаналізовано погляди науковців щодо виокремлення ключових ознак неподаткових надходжень бюджету та вказано на їхній суперечливий характер. Доведено, що більшість ознак неподаткових надходжень мають вибірковий характер, у зв’язку з чим запропоновано відмежовувати ці доходи від податкових надходжень виключно за ознакою їхнього стосунку до системи оподаткування. Наведено основні ознаки, за якими класифікують неподаткові надходження бюджету, та обґрунтовано доцільність їхнього розмежування за джерелами походження. Горин В. П. Теоретические основы неналоговых доходов бюджета. Обобщено научные подходы к раскрытию сущности неналоговых поступлений бюджета, указаны их дискуссионные моменты. Проанализированы мышления ученых на предмет выделения ключевых признаков неналоговых поступлений бюджета и указано на их противоречивый характер. Доказано, что большинство признаков неналоговых поступлений имеют избирательный характер, в связи с чем предложено отделять эти доходы от налоговых поступлений бюджета, исключительно по признаку их отношения к системе налогообложения. Приведены основные признаки, по которым классифицируют неналоговые поступления бюджета и обоснована целесообразность их разграничения в соответствии с источникам происхождения. Goryn V. Theoretical aspects of non-tax budget revenues. The deepening of economic crisis draws attention to the studying of non-tax revenues. However, despite the significant value that played non-tax revenues to government revenue, research of their nature and purpose, key features and approaches to classification barely underway. It is difficult to develop recommendations to improve their use of technology in public practice. The purpose of the article is to reveal scientific approaches to the essence interpretation of non-tax budget revenues and allocation of their main characteristics, existing approaches to characterize the distribution of non-tax budget revenues on various grounds of classification and propose its own approach. Evaluation of scientific approaches to disclosure of non-tax budget revenues indicated that the most common in the scientific literature is their interpretation as a finance law notion. According to the economic nature of non-tax revenues is almost not considered in the scientific literature. Found that the main features of tax revenues often attributable not coercive payment equivalence, irregular income and others. This approach is controversial, because most signs of identification are not relevant to the totality of tax revenues, but only to some of their parts. However, because of the signifi cant differences between different types of non-tax revenues under the terms of the accumulation of funds, meaning, purpose, to provide universal sign of their identification difficult. Non-tax revenues are classified in many ways: the legal nature, a fiscal nature, coupled with the state (municipal) property and others. However, this list of feature classification can not be completed and can be extended with additional features. It is proved that non-tax revenues from tax revenues advisable distinguished solely on the basis of their affiliation or non-affiliation to taxation system. Proposed to subdivide non-tax revenues by source of origin of the following groups: receipts from the state business activities; receipts from the sale of state property rights; revenues from administrative and regulatory activities; revenues from the provision of public services.